Modifiable Risk Factors for Delirium in Critically Ill Trauma Patients: A Multicenter Prospective Study. (April 2019) - Duceppe, Marc-Alexandre; Williamson, David R.; Elliott, Audrée; Para, Mélissa; Poirier, Marie-Christine; Delisle, Marie-Soleil; Deckelbaum, Dan; Razek, Tarek; Desjardins, Monique; Bertrand, Jean-Claude; Bernard, Francis; Rico, Philippe; et al.
Objective: Intensive care unit (ICU)–acquired delirium has been associated with increased morbidity and mortality. Prevention strategies including modification of delirium risk factors are emphasized by practice guidelines. No study has specifically evaluated modifiable delirium risk factors in trauma ICU patients. Our goal was to evaluate modifiable risk factors for delirium among trauma patients admitted to the ICU. Design: Prospective observational study. Setting: Two level 1 trauma ICU centers. Patients: Patients 18 years of age or older admitted for trauma including mild to moderate traumatic brain injury were eligible for the study. Interventions and Measurements: Delirium was assessed daily using the confusion assessment method for the ICU (CAM-ICU). The effect of modifiable risk factors was assessed using multivariate Cox regression analysis adjusting for severity of illness and significant nonmodifiable risk factors. Main Results: A total of 58 of 150 recruited patients (38.7%; 95% confidence interval [CI] 30.9-46.5) screened positive for delirium during ICU stay. When adjusting for significant nonmodifiable risk factors, physical restraints (hazard ratio [HR]: 2.13; 95% CI: 1.07-4.24) and active infection or sepsis (HR: 2.12; 95% CI: 1.18-3.81) significantly increased the risk of delirium, whereas opioids (HR: 0.35; 95% CI: 0.13-0.98), episodes of hypoxia (HR: 0.55; 95% CI: 0.31-0.95), access to a television/radio in the room (HR: 0.26; 95% CI: 0.11-0.62), and number of hours mobilized per day (HR: 0.77; 95% CI: 0.68-0.88) were associated with significantly less risk of delirium. Conclusion: We have identified modifiable risk factors for delirium. Future studies should aim at implementing strategies to modify these risk factors and evaluate their impact on the risk of delirium.